Age Estimation from Mandibles in Malay: A 2d Geometric Morphometric Analysis - Nur Ariessa Farhana Zulkifli; Nur Aliya Syuhada Mohd Saaid; Aspalilah Alias; Nurjehan Mohamed Ibrahim; Choy Ker Woon; Arofi Kurniawan; Beshlina Fitri Widayanti Roosyanto Prakoeswa (Elsevier B.V, 2024)
Indexed by WOS/ Scopus